Dietary proteins: from evolution to engineering - Daniel, Hannelore (Frontiers in Nutrition, 2024)
Because of the indispensable amino acids dietary proteins are the most important macronutrients. Proper growth and body maintenance depends on the quantity and quality of protein intake and proteins have thus been most crucial throughout evolution with hominins living in quite diverse food ecosystems. Developments in agriculture and food science have increased availability and diversity of food including protein for a rapidly growing world population while nutrient deficiencies resulting in stunting in children for example have been reduced. Nevertheless, the developing world and growing population needs more protein of high quality -with around 400 million tons per annum estimated for 2050. In contrary, protein consumption in all developed countries exceeds meanwhile the recommended intakes considerably with consequences for health and the environment. There is a growing interest in dietary proteins driven by the quest for more sustainable diets and the increasing food demand for a growing world population. This brings new and novel sources such as algae, yeast, insects or bacteria into play in delivering the biomass but also new technologies such as precision fermentation or in vitro meat/fish or dairy. What needs to be considered when such new protein sources are explored is that proteins need to provide not only the required amino acids but also functionality in the food produced thereof. This review considers human physiology and metabolism in the context of protein intake from an evolutionary perspective and prospects on future protein production.